2010
DOI: 10.1007/s10344-010-0442-5
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of otter Lutra lutra road mortality in a landscape abundant in lakes

Abstract: In order to reduce otter (Lutra lutra) road mortality and to predict accident sites, we assessed the localities of traffic accidents involving otters in the Uckermark County, Brandenburg, Northeast Germany. Eighty-eight otter accident sites from the years 1990 to 2003-as recorded by the Naturschutzstation Zippelsförde des Landesumweltamtes Brandenburg (Brandenburg State Office for Environment)-were categorised according to traffic and road patterns, otter habitat suitability, as well as presence and type of wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…This aggressive behaviour is particularly observed during the breeding season when competition for mates can lead to confrontations or when resources are limited [4,8]. In some instances, injuries can result from more aggressive interactions, especially when individuals are defending territories or asserting dominance within their social groups [33,48]. Also, these injuries sustained during conflicts may increase vulnerability to other threats such as predation, disease, or environmental hazards.…”
Section: Discussionmentioning
confidence: 99%
“…This aggressive behaviour is particularly observed during the breeding season when competition for mates can lead to confrontations or when resources are limited [4,8]. In some instances, injuries can result from more aggressive interactions, especially when individuals are defending territories or asserting dominance within their social groups [33,48]. Also, these injuries sustained during conflicts may increase vulnerability to other threats such as predation, disease, or environmental hazards.…”
Section: Discussionmentioning
confidence: 99%
“…This percentage is consistent with evidence from larger datasets obtained in Europe and in the Mediterranean basin [ 41 , 67 , 68 ]. Vehicle collision represents the most recorded cause of otter mortality across Europe [ 69 ], but their impact on otter populations is difficult to estimate (but see [ 70 ]). Some authors [ 17 , 25 ] reported a positive correlation between the rise of recorded road kills and the increase in population size, or geographic expansion, thus suggesting that traffic could have a minor impact on the survival of healthy populations [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Los atropellos se vinculan con los puntos de cruce entre carreteras de alta densidad y cursos de agua (más de dos tercios se produce en una banda de 100 metros de anchura en torno al cauce), con una mayor tasa de atropellos en machos . También en las proximidades de lagos o incluso en zonas sin cursos de agua en las inmediaciones, lo que podría ser el resultado de desplazamientos más largos entre parches favorables en zonas con abundancia de lagos (Jancke & Giere 2011). Los atropellos se concentran durante los meses de invierno y primavera, pudiendo tener un importante impacto sobre las poblaciones (Guter et al 2005).…”
Section: I4 Mortalidad Por Atropellounclassified